Pisum sativum L. subsp. sativum NGB 24082 ... - GLIS Of The ITPGRFA (Nordgen, 2024)
Plant Genetic Resource. Taxonomy: Pisum sativum L. subsp. sativum Common name(s): Pea Other names: Nordland Conserved by: Nordgen (NORDGEN), Sweden Local sample unique identifier: NGB 24082 Method of creation: Acquisition Date: 2012-06-20 Historical: No Biological status: Advanced or improved cultivar MLS status: Included ...